Do Occupational Demands Explain the Educational Gradient in Health? - Sophie-Charlotte Meyer; Annemarie Künn-Nelen (Institute for the Study of Labor (IZA), 2014)
The aim of this paper is to investigate to what extent occupation-specific demands explain the relationship between education and health. We concentrate on ergonomic, environmental, psychical, social and time demands. Merging the German Microcensus 2009 data with a dataset including detailed occupational demands (German Employment Survey 2006), we have a unique dataset to analyze the mediating role of occupational demands in the relationship between education and health status on the one hand and education and health behavior (BMI and smoking) on the other. We base our analyses on the entire working population and therefore also include those who no longer work, taking occupational demands related to their last job. First, we find that occupational demands are significantly related to subjective health and health behaviors. This holds even stronger for those who are no longer employed. Second, we find that whereas occupational demands do not explain educational differences in subjective health status, they do partially mediate the education gradient in the considered health behaviors. Educational differences in smoking status can partly be explained by ergonomic, environmental, psychical and social demands. The educational gradient in BMI is partly attributable to social occupational demands.
Keywords: I1; J2; I2; 330; education; occupational demands; working conditions; occupations; health; health behavior